Children’s coping with pain during dental care - Versloot J, Veerkamp JSJ, Hoogstraten J, Martens LC. (Blackwell Synergy, 2004)
The purpose of this study was (i) to assess the coping strategies of 11-year-old children when dealing with pain at the dentist, (ii) to determine the extent to which the level of the children’s dental fear and their experience with pain at the dentist are related to their ability to cope and their choice of strategies, and (iii) to analyse the possible differences between subsamples concerning dental caries.